Perencanaan Lanjutan Pembangunan Rumah Dinas Dan Utilitas Kantor UPP Kelas II Pomako, Mimika-Papua Tengah - Frederik Irsan Delu; Oktavianty Batto'; Benny Passambuna (Politeknik Amamapare Timika, 2025)
This Community Service Program aims to support the advanced planning of official housing and office utility development at the Port Authority Unit (UPP) Class II Pomako, Mimika Regency, Central Papua. The activity is motivated by the need for adequate housing for employees and reliable office utility systems to support port services. The implementation method includes field surveys, collection of technical and non-technical data, analysis of space and utility requirements, and formulation of planning recommendations adapted to the coastal conditions of Mimika. The results indicate that advanced planning should consider sustainability aspects, resilience to coastal environmental conditions, clean water availability, sanitation systems, electricity networks, and occupant comfort and safety. This program is expected to provide UPP Class II Pomako with practical planning recommendations as a basis for future development decisions.